The Knitted Fabric of Finland: Contemporary Handcrafted Wooly Socks Depicting the Nation State. (2nd April 2020) - Kouhia, Anna
Abstract: Textiles have played a key role in local and national cultures not only because of their utility and functionality, but also in terms of the symbolic value that they have for a particular social group, populace, or nation. Given the erratic and myriad nature of these communities, the focus of this article is on mapping out differentiation in the designs of contemporary wooly socks that find their source of inspiration in an imaginary of Finland celebrating its national centenary in 2017. In this endeavor, the article refines how an idea of a nation is reflected on through knitted craftwork, and how the divergence and layeredness of these designs not only reaffirms and evokes traditions but also develops the culture of knitting in contemporary times. In conclusion, the article contributes to the decoding of a textile design process in reflection of the recollection of the experiences of rootedness, the reproduction of the expression and the use of communicative images, and the negotiation of hybrid social realities voiced through the materiality of making.